Antiracism in Cuba : the unfinished revolution - Benson, Devyn Spence (Envisioning Cuba., 2016)
"Analyzing the ideology and rhetoric around race in Cuba and south Florida during the early years of the Cuban revolution, Devyn Spence Benson argues that ideas, stereotypes, and discriminatory practices relating to racial difference persisted despite major efforts by the Cuban state to generate social equality. ... examines 1960s government programs and campaigns against discrimination, showing how such programs frequently negated their efforts by reproducing racist images and idioms in revolutionary propaganda, cartoons, and school materials"--